Putting the National Back into Forest-Related Policies: The International Forests Regime and National Policies in Brazil and Indonesia - Singer, B. (2008)
The impact of the international forests regime (IFR) in shaping national forest-related policies (FRPs) is often considered as one of the key indicators of its effectiveness. This study is based on a comparison of the evolution over the past three decades of FRPs and the IFR's impact in Brazil and Indonesia — the two top-ranking countries in deforestation figures — and draws two conclusions. First, far from acting as a mere source of resistance to the IFR, the domestic policy context determines both the extent and type of impact of the IFR on FRPs. Secondly, FRPs also influence the IFR, which contradicts the top-down vision put forward by attempts to evaluate the IFR's effectiveness. This suggests that instead of a hierarchical relationship, the link between the national and international spheres is a dynamic one where the IFR and FRPs mutually adjust to each other according to the specificities of policy networks at both levels.